Evaluating the influence of light intensity in mcyA gene expression and microcystins production in toxic strains of Planktothrix agardhii and Microcystis aeruginosa - Salvador, Daniel (2018)
Cyanobacteria are phytoplanktonic organisms widely occurring in freshwaters, being frequently associated with the production of toxins, especially microcystins (MCs). MCs are produced non-ribosomally by a multienzyme complex (mcy genes). It has been reported that environmental factors, such as light intensity, can influence toxin production. The aim of this study was to assess the influence of light intensity in the transcription of the mcyA gene and corresponding production of microcystins in toxic isolates of Planktothrix agardhii, where little is known, and compare them to Microcystis aeruginosa.